Understanding the Syrian Educational System in a Context of Crisis - Mohammed Al Hessan; Stephanie Bengtsson; Judith Kohlenberger (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2016)
Up until the outbreak of conflict in 2011, Syrian young people were among the most educated in the Middle East region, with Syria having achieved near universal primary education enrolment and a high rate of completed secondary education. Due to the years of conflict, many Syrian are currently displaced within their country and across Syria's borders. In 2015, large numbers made their way across Europe and applied for asylum in Germany, Austria, Sweden, etc. The Syrian crisis raises important education-related questions for the international community as a whole, like the educational background of Syrians currently on the move. This paper gives an overview of the Syrian educational system in order to build an understanding of Syrian education in the broader global context. It aims to provide detailed information that other researchers, policymakers, and practitioners can draw from to inform their own work. The current document was written within the framework of DiPAS (Displaced persons in Austria survey), a survey carried out in and around Vienna to study the socio-demographic characteristics, values and attitudes of asylum seekers arriving in Austria in 2015.
Keywords: 300; Syria; education; educational system; crises